Optimalisasi Aplikasi Google Maps sebagai Alternatif Media Promosi pada UMKM di Shelter Taman Sriwedari - Salman Faris Insani; Yoppi Syahrial; Ardian Prima Putra (Warta LPM, 2022)
The Surakarta City Government built the Taman Sriwedari Culinary Shelter to accommodate MSMEs due to the relocation. Most of these MSMEs had to start from scratch because of the loss of customers and the low interest of visitors because most people did not know about the shelter’s existence. The main problem for partners is limited knowledge in marketing and promotion. This service aims to transfer science and technology to MSMEs by implementing mentoring activities in marketing and advertising. The solution to the problem is to optimize information technology based on Google Maps as an alternative media for promoting MSMEs at the Taman Sriwedari culinary shelter. Using this technology, it is hoped that the location of MSME partners will be easier to reach and increasingly known by the public. The method carried out is divided into five stages: initial socialization of the benefits of the google map application as an alternative media promotion, counseling and training on the practice of making, optimizing, and managing google map accounts, addresses on google maps, sharing locations from google maps, and adding photos & reports. Social media on google maps. To identify an increase in the knowledge of MSME partners regarding the material presented, a pretest and posttest were carried out. After the training was held, the impact was that MSME partners experienced increased knowledge according to the target. The evaluation results at each stage of the activity, the showed that the post-teste increased 25% compared to the pretest score. In addition, the outcome of this activity is the ownership of a Google Maps account that has been optimized for each participant. Based on the indicators that have been measured, it can be concluded that this training & mentoring activity is categorized as successful. The expected follow-up in the future is that partners can optimize the use of the Google Map application as an alternative media for promotion independently and sustainably. The hope is that the location of their MSMEs will be more easily accessible and known by the wider community. Partners are also advised not to hesitate to actively discuss with the Univet Bantara Community Service Team if they encounter obstacles.